2016
DOI: 10.14712/23362936.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches in Pilonidal Sinus Treatment

Abstract: Pilonidal sinus is a very common inflammatory disease of the gluteal region. The ideal method of pilonidal sinus treatment should have a low recurrence rate with minimum excision. Moreover, the treatment method should have a short hospitalization time, should let the patient return to his normal life rapidly, should cause minimum loss of labour and should result a small scar only. In the presented review, modalities in pilonidal sinus treatment in the light of current information in the literature are evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
(45 reference statements)
0
40
0
Order By: Relevance
“…Studies have shown that chemokines play an important role in tumor growth and angiogenesis. 33,34 Studies have shown that calcium signaling pathways are associated with the development and progression of various cancers, such as lung adenocarcinoma, 35 breast cancer, 36 colorectal cancer, 37 Burkitt's lymphoma, 38 and others. 2 genes were upregulated genes and 3 genes were downregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that chemokines play an important role in tumor growth and angiogenesis. 33,34 Studies have shown that calcium signaling pathways are associated with the development and progression of various cancers, such as lung adenocarcinoma, 35 breast cancer, 36 colorectal cancer, 37 Burkitt's lymphoma, 38 and others. 2 genes were upregulated genes and 3 genes were downregulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…The drainage of pilonidal sinus abscess should be acknowledged as an essential part of therapy to eliminate the primary focus of the infection 14 18. Several surgical methods are used to treat pilonidal sinus, such as primary suture, lay open and the flap plasty techniques 19. Each method has a certain recurrence rate and, therefore, no standard treatment approach has been determined, despite the high incidence of pilonidal disease affecting young population 19…”
Section: Discussionmentioning
confidence: 99%
“…In patients with extensive perianal disease or rectal involvement, transperineal completion proctectomy is often feasible, thereby avoiding relaparotomy. By using a close rectal intersphincteric resection, damage to the pelvic autonomic nerves is avoided [19,[53][54][55][56][57][58][59].…”
Section: New Developmentsmentioning
confidence: 99%